Women’s Communal Spirituality in the Gebluk Tradition: Understanding Living Islam through Local Religious Practices - Miftakhus Sifa' Bahrul Ulumiyah; Nur Kholis; Abdullah Haidar (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study examines Gebluk as a form of Living Islam practiced by a rural Muslim community in Kalisat Village, Pasuruan, East Java. Previous research has emphasized Gebluk as a medium of da'wah, Islamic education, and cultural preservation, while giving limited attention to women’s communal religious learning and spirituality. The study analyzes how Gebluk transmits Islamic values, how women sustain the practice and develop practice-based authority, and how collective participation creates social and religious fellowship. Informed by Living Islam and religious ethnography, the qualitative study used participant observation, semi-structured interviews with seven purposively selected informants, chant manuscripts, and field documentation collected in 2019. Digital documentation and online reports were used only as secondary contextual evidence. Data were analyzed through condensation, display, and conclusion drawing, supported by triangulation and limited member checking. The findings show that Gebluk chants communicate aqidah, fiqh, and akhlaq through repetition, memorization, embodied participation, and peer learning. Women organize meetings, lead and teach chants, mentor new members, and preserve the tradition across generations, thereby exercising practical agency and practice-based religious authority. The strongest evidence of communal spirituality lies in repeated collective chanting, bodily coordination, shared learning, silaturahmi, and mutual support, rather than in uniform mystical or intense emotional experience. Gebluk therefore functions as a pedagogical, spiritual, and social space in which Islam is lived through the interaction of religious teachings and local culture. The study contributes to Living Islam scholarship by showing how women’s communal religious work sustains Islamic learning, fellowship, and tradition at the local level.